1995
DOI: 10.1093/rheumatology/34.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Circulating Intercellular Adhesion Molecule-1 and -3 but Not Circulating Endothelial Leucocyte Adhesion Molecule Are Increased in Patients With Rheumatoid Vasculitis

Abstract: The aim of this study was to investigate whether levels of circulating adhesion molecules reflect vascular inflammation in rheumatoid vasculitis (RV). Levels of circulating intercellular adhesion molecule-1 (cICAM-1), c-ICAM-3 and circulating endothelial leucocyte adhesion molecule (cE-selectin) were determined in 14 patients with RV and compared to 47 patients with rheumatoid arthritis (RA) and 100 healthy donors (HD). Enzyme-linked immunosorbent assays were used to quantify cICAM-1, cICAM-3 and cE-selectin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
2
23
0
2
Order By: Relevance
“…This is in agreement with previous papers [5,6] whereas other studies have reported elevated levels in this condition [7,8]. Our RA patients were older than the SpA patients and controls, but Cush et al [4] and Kuryliszyn-Moskal et al [8] did not find a correlation between slCAM-1 and age in RA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous papers [5,6] whereas other studies have reported elevated levels in this condition [7,8]. Our RA patients were older than the SpA patients and controls, but Cush et al [4] and Kuryliszyn-Moskal et al [8] did not find a correlation between slCAM-1 and age in RA.…”
Section: Discussionsupporting
confidence: 93%
“…In rheumatoid arthritis (RA), several studies have reported normal [5,6] or elevated levels of sICAM-1 [4,7] with sometimes a weak correlation with disease activity [4] or extra-articular features such as vasculitis [5,8]. In a previous study [9] we found an increased expression of LFA-1 on the surface of granulocytes in spondylarthropathies and LFA-1 expression correlated with total IgA levels in the serum of these patients.…”
mentioning
confidence: 60%
“…The ICAM-1 protein, TNF-, and E-selectin are expressed in ECs and perivascular mononuclear cells in areas of microvascular damage in the salivary glands of RV patients (Flipo et al 1997). Furthermore, RV patients have elevated levels of sICAM-1 (Voskuyl et al 1995;Kuryliszyn-Moskal, Bernacka et al 1996;Witkowska et al 2003). In addition, Voskuyl et al (Voskuyl, Martin et al 1995) demonstrated the involvement of ICAM-3 and ICAM-1 in patients with RV.…”
Section: Icam-1mentioning
confidence: 99%
“…Furthermore, RV patients have elevated levels of sICAM-1 (Voskuyl et al 1995;Kuryliszyn-Moskal, Bernacka et al 1996;Witkowska et al 2003). In addition, Voskuyl et al (Voskuyl, Martin et al 1995) demonstrated the involvement of ICAM-3 and ICAM-1 in patients with RV. This involvement suggests that ICAM-1 and ICAM-3 in serum may be useful markers of vascular inflammation in patients with RV, and these proteins may play a crucial role in vasculitis development in RA.…”
Section: Icam-1mentioning
confidence: 99%
“…В развитии васкулита при РА могут участвовать моле-кулы межклеточной адгезии 1 (ICAM1), Е-селектин и фак-тор некроза опухоли α (ФНОα) [18,19].…”
unclassified